Evaluasi Kesesuaian Penempatan PPPK Berdasarkan Analisis Jabatan dan Analisis Beban Kerja: Studi Kasus pada BAWASLU - Nugrahaningtyas, Ika Ardhile; Zulianti, Naili; Humardani, Syah Rizal (Indonesian Journal of Humanities and Social Sciences, 2025)
This research evaluates the suitability of PPPK (Government Employees with Work Agreements) placement at Bawaslu based on Job Analysis (Anjab) and Workload Analysis (ABK). This study discusses issues related to the mismatch between the competencies of PPPK in 2024 and the qualifications of the positions they occupy, which has the potential to hamper organizational effectiveness. The novelty of this study lies in the empirical testing of the relationship between Anjab, ABK, and employee suitability for positions (person job fit) among PPPK at Bawaslu. A mixed method approach was used in this study, including a survey of 1,400 PPPK and in-depth interviews with HR policy makers at Bawaslu. Regression analysis results show that Anjab and ABK have a positive and significant effect on placement accuracy, with Anjab having a relatively stronger influence (coefficient of 0.479). However, qualitative findings confirm that the implementation of Anjab and ABK at Bawaslu is still administrative in nature and has not been used as a strategic instrument to reflect the actual quantitative needs of employees. This study emphasizes the need to update Anjab and ABK based on actual data, integrate competency mapping, and strengthen the merit system so that PPPK placement is more accurate.